(untitled) (Research, Society and Development, 2022)
Leptospirosis is a zoonosis caused by pathogenic bacteria of the genus Leptospira. This disease affects several animals and humans. Symptoms of leptospirosis can range from mild to severe, may in some cases lead to death. For the diagnosis of leptospirosis, the microscopic agglutination test is considered the “gold standard”; however, it has limitations and studies are being conducted to develop alternative methods of screening and diagnosis of leptospirosis. Serological and immunochemical tests using Leptospira recombinant antigens in combination to molecular tests may be an alternative. In this study, we reported the advances achieved from 2014 until 2020 in controlling leptospirosis based on serological tests using recombinant antigens and molecular diagnosis.